Evaluating the Effectiveness of Intravesical Instillation of BCG by Modified Maintenance Method in Patients With High-Risk Ta and T1 Bladder Cancer: A Randomized Clinical Trial - Nasser Shakhssalim; Mehdi Dadpour; Farzaneh Sharifiaghdas; Behzad Narouie; Sajjad Askarpour Kabir; Ehsan Sepehran; Ramin Borabadi; Nasrin Borumandnia; Hamidreza Rouientan; Abbas Basiri (Clinical Medicine Insights: Oncology, 2023)
Background: It is estimated that 75% of urothelial bladder cancers are non–muscle-invasive cancers (NMIBCs). The development of more effective methods for optimizing the management of this subset of patients is of paramount importance. This study aimed to evaluate the effectiveness and side effects of modified maintenance Bacillus Calmette-Guérin (BCG) therapy in patients with high-risk NMIBC. Methods: A total of 84 patients with NMIBC who met the inclusion criteria were randomly divided into 2 groups of 42 patients after receiving intravesical BCG weekly, 1 month after transurethral resection of the bladder tumor (TURT) for 6 weeks as the induction. In group I, patients continued monthly intravesical instillation of BCG for 6 months as maintenance, whereas group II patients did not. All patients were followed up for recurrence and progression for 2 years. Results: Although the recurrence rate was lower in group I (16.7% vs 31%), there was no significant difference among groups (P = .124). Pathology progression was also lower in group I (7.1% vs 11.9%) with no significant difference among groups (P = .713). Complications were not statistically different among groups (P = .651). A statistically significant difference was not observed between the groups in the acceptance rate of patients (97.6% in group I vs 100% in group II). Conclusions: The recurrence rate and progression rate in NMIBC patients with maintenance-free induction therapy after TURT were almost twice as high as those with 6-month maintenance therapy; however, it was not statistically significant. Modified BCG maintenance protocol made favorable compliance for patients. Trial registration: This study was retrospectively registered at Iranian Registery of Clinical Trials with the code IRCT20220302054165N1.